2018 Data Breach Investigations Report: the year of ransomware. Issue 5 (May 2018) - Unknown
Abstract : While many security specialists believe that the peak of the ransomware plague has passed, with cyber-criminals focusing more on crypto-mining and crypto-jacking, that particular form of malware nonetheless features large in the 11th edition of Verizon's annual Data Breach Investigations Report (DBIR).